Strengthening relationships with customers in online pharmacies as links of pharmaceutical value networks - Pecinová, Zuzana; Čurdová, Markéta; Lošťáková, Hana; Rajhelová, Hana (University of Pardubice, 2011)
An effective management strategy in today's highly competitive environment is strengthening long-term relationships with customers. The essence of this strategy is building and developing relationships with customers on the principle of mutual benefit aiming to achieve higher customer satisfaction and loyalty. An important role in strengthening the relationships with customers is played by information technologies; in recent years the Internet has become increasingly important in this area. This article presents the results of a primary qualitative research, which focused on defining the appropriate forms and tools for strengthening customer relationships in online pharmacies and the extent of their application in the Czech Republic, evaluating their effectiveness and possibilities of their further use in developing relationships with customers.